Analysis of Community Awareness Against Threats to Personal Data Security Through Phishing Websites - M Alvian H Nasution; Joko Dwi Santoso (STMIK Budi Darma, 2021)
The threat of personal data security is a very sensitive matter lately, Website Phishing is one of the activities that can trap and threaten someone by deceiving that person. From the results of the Phishing Website, the victim indirectly provides data or information about the victim to the trapper. In this case, Phishing Websites are one of the cyber crimes that are still very often used to retrieve victim data.